8m+5n-6m+8n=

Simple and best practice solution for 8m+5n-6m+8n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8m+5n-6m+8n= equation:


Simplifying
8m + 5n + -6m + 8n = 0

Reorder the terms:
8m + -6m + 5n + 8n = 0

Combine like terms: 8m + -6m = 2m
2m + 5n + 8n = 0

Combine like terms: 5n + 8n = 13n
2m + 13n = 0

Solving
2m + 13n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-13n' to each side of the equation.
2m + 13n + -13n = 0 + -13n

Combine like terms: 13n + -13n = 0
2m + 0 = 0 + -13n
2m = 0 + -13n
Remove the zero:
2m = -13n

Divide each side by '2'.
m = -6.5n

Simplifying
m = -6.5n

See similar equations:

| (x+9)(x+12)=0 | | 7m+2n-2m+11n= | | x-80=40 | | 5.7m-3=2.7m+6 | | 1.45x+7(0.15x-2.8)=14.4 | | 5x-2=-18-3x | | 13-2x-5x+9= | | 2.5x-(40+1.75x)=550 | | 0.7=0.4+x-0.35 | | 20x+12=0 | | 16+2(x+4)(x-4)-x=-x+16 | | 6(y-1)-2y=2(2y-3) | | 0.7=0.4+P(B)-0.35 | | .25x-.75y=-1 | | 7.4x-4-5.2x=2.6 | | 4(5x+4)=3x+36+7x | | x^2+3y=-1 | | 8(m+6)+4=36+5m | | -3.6x+1.3=-16.7 | | 21x+6=23x-2 | | G(x)=x^2-x-5 | | -2.1-1.5=x+1.3 | | 3=t+5-3t | | 4x-5=6x+3 | | 2(x+5)=2x-5 | | 6=v+0.84 | | -50-0.25=-75 | | 110x=90(2-x) | | 1.29+3.9-9.99+6.1= | | X-3(x-5)=2x-11 | | 5y-x=-1 | | W^3+w^2-2w=8 |

Equations solver categories